Morphology, Morphogenesis and Phylogenetic Position of the Soil Hypotrichous Ciliate, Parabistichelladieckmanni (Foissner, 1998) Foissner, 2016 (Ciliophora, Hypotrichia), with Notes on the Phylogeny of Parabistichella. (16th December 2020) - Lyu, Zhao; Li, Jingbao; Wang, Yurui; Shao, Chen
Abstract: The morphology, morphogenesis and molecular phylogeny of Parabistichella dieckmanni (Foissner, 1998) Foissner, 2016, isolated from north China, were investigated. The Chinese population was characterized as having five to seven frontal cirri in corona, four to seven buccal cirri arranged in a row, two to four short frontal rows and two long frontoventral rows, three to seven transverse cirri, four macronuclear nodules, three dorsal kineties following a Gonostomum ‐pattern, and caudal cirri absent. Morphogenetic research reveals that the main characteristics during binary fission are as follows: (1) the long left frontoventral row is formed by two or three anlagen; (2) the posterior part of the parental adoral zone of membranelles is renewed, and the oral primordium of the opisthe is formed intrakinetally; (3) FVT‐anlagen I to VI (or V, VII) produce each a frontal cirrus to form the frontal corona; (4) development of dorsal kineties follows the Gonostomum ‐pattern. Phylogenetic analyses showed that P . dieckmanni does not group with other Parabistichella species. Therefore, the genus Parabistichella is polyphyletic. Additionally, Parabistichella variabilis n. comb. (basionym: Bistichella variabilis He & Xu, 2011) and Parabistichella cheni n. nom. (basionym: Parabistichella variabilis Jiang et al., 2013) were suggested.